1996
DOI: 10.1037/0022-006x.64.3.532
|View full text |Cite
|
Sign up to set email alerts
|

The role of the therapeutic alliance in psychotherapy and pharmacotherapy outcome: Findings in the National Institute of Mental Health Treatment of Depression Collaborative Research Program.

Abstract: The relationship between therapeutic alliance and treatment outcome was examined for depressed outpatients who received interpersonal psychotherapy, cognitive-behavior therapy, imipramine with clinical management, or placebo with clinical management. Clinical raters scored videotapes of early, middle, and late therapy sessions for 225 cases (619 sessions). Outcome was assessed from patients' and clinical evaluators' perspectives and from depressive symptomatology. Therapeutic alliance was found to have a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
400
4
11

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 672 publications
(439 citation statements)
references
References 25 publications
(32 reference statements)
24
400
4
11
Order By: Relevance
“…It has been shown that the therapeutic alliance is strongly and positively related to outcome in drug treatment, just as it is in psychotherapy [144]. One reason may be that the drug condition usually involves weekly contact combined with supportive psychotherapy [145], a higher level of drug treatment than is usually delivered in the typical outpatient setting.…”
Section: Belief No 4: Antidepressants Are More Effective Than Psychomentioning
confidence: 99%
“…It has been shown that the therapeutic alliance is strongly and positively related to outcome in drug treatment, just as it is in psychotherapy [144]. One reason may be that the drug condition usually involves weekly contact combined with supportive psychotherapy [145], a higher level of drug treatment than is usually delivered in the typical outpatient setting.…”
Section: Belief No 4: Antidepressants Are More Effective Than Psychomentioning
confidence: 99%
“…A positive early therapeutic alliance has been shown repeatedly to be a good predictor of outcome in psychotherapy (Horvath, 2005;Horvath & Symonds, 1991). Indeed, in an analysis of the role that the therapeutic alliance played in the brief treatments for depression, the TDCRP and Krupnick et al (1996) found that the quality of the therapeutic alliance was a better predictor of outcomes than any of the specifi c techniques and tactics in the treatment manuals. Hence, the quality of the treatment relationship established early in treatment is probably the key factor contributing to the therapeutic gain in the brief outpatient treatment of serious depression.…”
Section: Childhood Traumamentioning
confidence: 99%
“…Therapeutic alliance early in treatment has been shown to be associated with outcomes (Krupnick et al, 1996), indicating that this is a critical precursor for clients making therapeutic gains in treatment. In addition, studies show us that clients' pretreatment expectancy for change and early homework compliance are important mediators of treatment outcome and can serve as motivation for therapeutic involvement and subsequent treatment gains (Westra, Dozois, & Marcus, 2007).…”
Section: Modifications Of the "Standard" Treatment: Format And Sessiomentioning
confidence: 99%